The Impact of Competitive/Comparative Learning Strategy for Learning Scout Camping Skill for Students of Physical Education and Sports Sciences - Hussein, Dr. Amna Fadel Mahmoud (International Journal of Psychosocial Rehabilitation, 2020)
The scientific progress and rapid technological development have made the new mission of the university to take special care of the way of thinking for its students away from monotony. Scouts studied by students in the Faculty of Physical Education and Sports Science for the first phase within the vocabulary of the curriculum and not to use the strategy of competitive/ comparative learning in the teaching of scout education, a lesson that little known students face It is somewhat difficult when they study the scouting skills of this subject and this study is the first using the competitive/ comparative learning strategy to learn the scout camping skill for the first stage students at the University of Babylon. Therefore, the researchers decided to go into this study using the strategy of comparative competitive learning to give the spirit of competition among students and achieve better learning, and to identify the extent of the strategy to learn the skill of scouting camping for students of the first stage at the University of Babylon, for students.